Perceraian Akibat Tindakan KDRT Di Pengadilan Agama Kendari Kelas 1A (Perspektif Maqashid Syariah): indonesia - Bolo, Gatra Mahe; Saputra, Nafar; Ramli, Arif Rahman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research examined the phenomenon of divorce due to domestic violence (DV) handled at the Religious Court of Kendari Class 1A, focusing on the analysis of causal factors, the basis for legal considerations by judges, and the relevance of the maqashid al-syariah approach in resolving the cases. This study employed a qualitative approach with a case study method. The primary data were obtained from observation, interviews with judges and related parties, and analysis of case documents. Meanwhile, the secondary data were collected through a literature review of books, journals, and laws and regulations. The purpose of this research was to provide a comprehensive understanding of the legal dynamics of divorce due to domestic violence (DV) and to explore the role of Shari'a values in decision-making. The results indicated that in the past four years, 2,466 divorce cases have been decided by the Religious Court of Kendari, 190 of which involved DV. Factors contributing to domestic violence (DV) included economic pressure, infidelity, deviant behavior, and poor communication within the household. In deciding cases, judges referred to Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law, Supreme Court instruments, and norms of fiqh and customary law. The maqashid al-shariah approach prioritized the principles of hifz al-nafs (protection of the soul) and hifz al-'ird (protection of honor), thus viewing divorce as an effort to save individuals from physical and psychological violence that could damage human dignity. This research demonstrates the importance of educating the public about the dangers of domestic violence, firm law enforcement against perpetrators, and preventive and rehabilitative programs for victims. The synergy between positive law and the values of maqashid al-shariah provides a strategic approach to realizing justice and well-being in resolving family disputes.